(untitled) (Colombia Medica, 1988)
The different levels in the nervous processing of pain afferents are revised. Outgoing from the spinal cord’s dorsal horn, two nervous fiber tracts are involved: the neospinothalamic and the paleospinothalamic. A pronounced divergence of the lateral spinothalamic tract fibers at the brainstem level forms interconnections with the limbic system. In the thalamus (ventral posterior nucleus), the organization of synapses of pain afferents is like in "archipelagos," linking pain afferents with touch and proprioceptive afferents. The role of the cerebral cortex is still not clear. There is no experimental support without controversies for the existence of a "cortical pain center."